Anxiety as a Common Biomarker for School Children With Additional Health and Developmental Needs Irrespective of Diagnosis - Cross, Alana Jade; Goharpey, Nahal; Laycock, Robin; Crewther, Sheila Gillard (Frontiers in Psychology, 2019)
“Additional needs children” is a term often used in the education system to describe children with school-based problems characterised by learning difficulties arising from academic, social and emotional stressors including, but not limited to, clinically diagnosed Neurodevelopmental Disorders (NDD). What has seldom been investigated is what biopsychosocial characteristics and other common comorbid behaviours are associated with academic learning difficulties. Thus, the aim of this study was to investigate the relationship between anxiety levels (Spence Children’s Anxiety Scale- Parent Report), autism traits (Autism Spectrum Quotient – Child Version) and sleep quality (Sleep Disturbance Scale for Children) in ‘additional needs children’ with a diagnosis of Autism Spectrum Disorder (ASD), Language Impairment or Mixed Diagnosis without an intellectual disability. The results demonstrated that the ASD group reported more impairments associated with comorbid anxiety and sleep compared to the other clinically diagnosed groups. Similarly, greater anxiety level was positively associated with a greater number of autism traits and poorer sleep quality regardless of diagnostic group. This suggests that higher anxiety symptoms are a core biomarker of children who often first come to their teacher’s attention with reading and learning difficulties (i.e. “additional needs”), irrespective of the primary cause of school-based problems.